Evolutionary lability underlies drought adaptation of Australian shrubs along aridity gradients - Xu, Gui-Qing; Kandlikar, Gaurav S.; Vaz, Marcel C. (Frontiers in Plant Science, 2022)
Leaf drought tolerance traits influence plant survival in water deficit conditions, and these traits are influenced by both the plant’s evolutionary history, and the environment in which the plant is currently growing. However, due to the substantial phenotypic plasticity in leaf traits, we still do not know to what degree the variation in leaf traits is governed by species’ phylogenetic history or by their environment. To explore this question, we re-examined a drought tolerance dataset from 37 native Australian shrub species with varying climate origins growing in a common garden located in Melbourne, Australia. We previously measured seven leaf morpho-physiological traits and here, we estimated how phylogenetically conserved these traits are. We quantified phylogen, and the strength of correlation between the morphological traits and physiological traits before and after accounting for shared phylogenetic history. We also evaluated the relationship between species’ leaf traits and the climate of their native ranges. We present three main findings: (a) most leaf drought tolerance traits had weak phylogenetic signals, which is consistent with convergent evolution of these traits. (b) There is weak but consistent coordination between distinct leaf drought tolerance traits, which can be masked due to species' phylogenetic histories. (c) Leaf drought tolerance traits show strong correlations with the climate of species’ origins, and this relationship is only weakly impacted by phylogenetic signals. Therefore, the role of phylogeny on the coordination among leaf functional traits and their links to climate were limited. A better understanding of trait-environment relationships might be more pivotal than understanding the evolution of these traits for improving predictions of species’ response to climate change-type drought, especially for shrub species that span substantial aridity gradients.